Allergic Reaction Following Implantation of A Blood Glucose Sensor - Müge Atar; Özgür Pirgon; Gülsüm Çetin (Galenos Publishing House, 2021)
Our patient, a seven-year-old boy, was followed with the diagnosis of type 1 diabetes since six years old, and he was started to check his blood glucose levels via The FreeStyle Libre 10 days ago. However, he developed severe pruritis after implantation. After removing the sensor, skin irritation and a local cutaneous reaction, probably allergic reaction to the sensor containing the latex was detected. The patient did not report a history of allergy to medications or adhesive tapes. The sensor patch was removed, and dermatitis was resolved by the application of topical creams containing corticosteroids.